Testicular mitochondrial alterations in untreated streptozotocin-induced diabetic rats - Amaral, Sandra (2009)
http://www.sciencedirect.com/science/article/B6W8G-4V3HFCC-2/2/73c61572e33e945983a6914b2dfbeb63